2022
DOI: 10.1029/2022gl098308
|View full text |Cite
|
Sign up to set email alerts
|

Crust and Uppermost Mantle Magma Plumbing System Beneath Changbaishan Intraplate Volcano, China/North Korea, Revealed by Ambient Noise Adjoint Tomography

Abstract: Studies of volcanoes are essential for understanding the internal structure of the Earth and its evolution. Holocene intraplate volcanism is widespread across northeast (NE) China, including Changbaishan volcano (CBV), Longgang volcano (LGV), and Jingpohu volcano (JPHV) as shown in Figure 1 (Liu et al., 2001). Mt. Changbaishan (also known as Mt. Paektu in Korean), straddling the border between China and North Korea, is located more than 1,000 km northwest of the Japan Trench along which the Pacific Plate is su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 53 publications
1
6
0
Order By: Relevance
“…Our 3‐D V p and V s models have higher resolution in the upper crust beneath the Tianchi volcanic area as compared with previous tomography results (Fan & Chen, 2019; Fan et al., 2022; H. Zhu et al., 2019). The identified volcanic earthquakes in Section 3.1 are also displayed in Figure 8 to get further insight into the linkage between the crustal magmatic system and volcanic seismicity.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…Our 3‐D V p and V s models have higher resolution in the upper crust beneath the Tianchi volcanic area as compared with previous tomography results (Fan & Chen, 2019; Fan et al., 2022; H. Zhu et al., 2019). The identified volcanic earthquakes in Section 3.1 are also displayed in Figure 8 to get further insight into the linkage between the crustal magmatic system and volcanic seismicity.…”
Section: Resultssupporting
confidence: 77%
“…A number of geophysical studies using 3‐D deep seismic sounding, 2‐D and 3‐D magnetotelluric sounding, 3‐D gravity modeling, and ambient noise tomography have been conducted to reveal locations and geometries of potential magma chambers beneath the CBV over the past two decades (Choi et al., 2013; Fan & Chen, 2019; Fan et al., 2022; Kim et al., 2017; Qiu et al., 2014; Tang et al., 2001; Yang et al., 2021; X. Zhang et al., 2002; H. Zhu et al., 2019). The 3‐D deep seismic sounding study revealed a low‐ V p zone at depths of 9–15 km beneath the Changbaishan‐Tianchi volcanic area, indicating the existence of a magma reservoir (X. Zhang et al., 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2010) shows a ∼4,300 km 3 LVL in the same area with a melt fraction of ∼32%. Relatively low melt fraction estimates can be caused by the resolution limits, the wavefront healing effect, and non‐uniqueness of seismic tomography techniques (Fan et al., 2022; Paulatto et al., 2019, 2022; Rasht‐Behesht et al., 2020). For instance, the wavefront healing effect can lead to ∼50% melt fraction underestimation (Paulatto et al., 2019).…”
Section: Interpretation and Discussionmentioning
confidence: 99%
“…In addition, relatively low melt fractions are reported for some volcanic regions, with estimates from 2% to 10% for the intra‐crustal LVLs with several‐kilometer thicknesses, for example, in Northeast Japan (K. X. Chen et al., 2020), Changbaishan volcano (Fan et al., 2022), and Marapi volcano (Nurfiani et al., 2021) (Figure 4e). Even for the same volcano, different studies show dramatic differences in melt fraction estimates.…”
Section: Interpretation and Discussionmentioning
confidence: 99%